Manajemen Produksi Tayangan Televisi “Talkcation” RBTV Jogja pada Periode Magang MBKM Tahun 2022 - Rivga Agusta; Satya Putra Ariyanto (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Talkcation is educational talkshow program in collaboration with Reksa Birama Televisi (RBTV) and Amikom Yogyakarta Communication Studies program in Merdeka Belajar Kampus Merdeka (MBKM) internship program. Talkcation comes with a new concept to provide a more interesting and educational. The purpose of this study is to explain the management strategy for the production of Talkcation shows during the 2022 MBKM internship period conducted by the Rumah Kreatif Media team. In this study, researchers used qualitative research types with case qualitative descriptive that focused on the 2022 MBKM period. The main data source comes from interviews with the Rumah Kreatif Media team who were observed during the research process in the field. This study can provide an overview and analysis related to the process of management from Rumah Kreatif Media to create a program television talkshow at RBTV Jogja. This was done in order to improve production from the results of Talkcation better, provide variations, and improvisation of programs for RBTV.